The Effects of Sago (Metroxylon sagu) Bark and Frond Waste as Substrates on the Growth and Yield of Grey Oyster Mushrooms (Pleurotus sajor-caju) - Haslinza, Senghie; Mohamad Hasnul, Bolhassan; Dayang Salwani, Awg-Adeni (Universiti Putra Malaysia Press, 2021)
This study was carried out to examine the effects of sago bark (SB) and sago frond (SF) waste on the growth and yield of grey oyster mushrooms (Pleurotus sajor-caju). Nine substrate formulas were studied, including sawdust (SD) alone as a control and the combination of 25:75, 50:50, and 75:25 ratios between SD and SB or SF. The results showed a significant difference in the total colonisation period, total fruiting body yield, and biological efficiency (BE). However, an insignificant difference was determined in the characteristics of the fruiting body for different substrate formulas. The substrates with the ratio of 50SD:50SF and 100 SD are the most suitable substrate formulas for the cultivation of P. sajor-caju. One hundred (100) SD achieved the fastest total colonisation period (24.44 days) but there was no significant difference with 75SD:25SF (24.78 days) and also obtained the fastest first harvest (50.33 days). However, 100SD produced a significantly lower total fruiting body yield (77.99 g/bunch) compared to 50SD:50SF, which produced the highest total yield (88.09 g/ bunch) and highest BE (17.62%) with a short total colonisation period (26.45 days). The substrates produced high values in cap diameter, stipe length, and effective fruiting bodies.